UNLOCKING THE POTENTIAL OF STRATEGIC HRM IN THE DIGITAL AGE: A CONCEPTUAL FRAMEWORK FOR DIGITAL TRANSFORMATION - Liang YuLing ,; Li SuHua ,; Qian HuiLin ,; Ooi Kok Loang, (Journal of Islamic, Social, Economics and Development, 2023)
The digital technology wave is driving the innovation of traditional management concepts, including Strategic Human Resource Management (SHRM), which has been questioned for its lack of a solid theoretical basis and implementation challenges. This paper proposes a conceptual framework for digital transformation in HRM based on the latest frontier theory in strategic management. The framework integrates strategic HRM and dynamic management capabilities, emphasizing the synergistic relationship between HR portfolio allocation, HR bundling, and HR leverage, as well as the important role of entrepreneurial orientation. The proposed framework attempts to integrate the various HRM functions from a holistic HR perspective and provides a comprehensive approach to HRM in a digital context. It aims to help organizations and individuals achieve holistic development and unlock the potential of SHRM in the digital age.